Rules for being a girl - Bushnell, Candace (London Macmillan Childrenś Books, 2020)
Marin is a smart, driven, popular girl - she's headed for Brown when she graduates and has a brilliant career as a journalist ahead of her. Especially in the eyes of English teacher Mr Beckett. He spends a lot of time around Marin, and she thinks it's harmless... until he kisses her.No one believes Marin when she tells them what happened, so she does the only thing she can: she writes an article called 'Rules for Being a Girl' for the school paper to point out the misogyny and sexism that girls face every day. As things heat up at school and in her personal life, Marin must figure out how to take back the power and rewrite her own rules.
Keywords: Publikácie pre dospelých